Delineation of the Crucial Evolutionary Amino Acid Sites in Trehalose-6-Phosphate Synthase From Higher Plants. (March 2020) - Wang, Rong; He, Congfen; Dong, Kun; Zhao, Xin; Li, Yaxuan; Hu, Yingkao
Trehalose-6-phosphate synthase (TPS) is a key enzyme in the biosynthesis of trehalose, with its direct product, trehalose-6-phosphate, playing important roles in regulating whole-plant carbohydrate allocation and utilization. Genes encoding TPS constitute a multigene family in which functional divergence appears to have occurred repeatedly. To identify the crucial evolutionary amino acid sites of TPS in higher plants, a series of bioinformatics tools were applied to investigate the phylogenetic relationships, functional divergence, positive selection, and co-evolution of TPS proteins. First, we identified 150 TPS genes from 13 higher plant species. Phylogenetic analysis placed these TPS proteins into 2 clades: clades A and B, of which clade B could be further divided into 4 subclades (B1-B4). This classification was supported by the intron-exon structures, with more introns present in clade A. Next, detection of the critical functionally divergent amino acid sites resulted in the isolation of a total of 286 sites reflecting nonredundant radical shifts in amino acid properties with a high posterior probability cutoff among subclades. In addition, positively selected sites were identified using a codon substitution model, from which 46 amino acid sites were isolated as exhibiting positive selection at a significant level. Moreover, 18 amino acid sites were highlighted both for functional divergence and positive selection; these may thus potentially represent crucial evolutionary sites in the TPS family. Further co-evolutionary analysis revealed 3 pairs of sites: 11S and 12H, 33S and 34N, and 109G and 110E as demonstrating co-evolution. Finally, the 18 crucial evolutionary amino acid sites were mapped in the 3-dimensional structure. A total of 77 sites harboring functionally and structurally important residues of TPS proteins were found by using the CLIPS-4D online tool; notably, no overlap was observed with the identified crucial evolutionary sites, providing positive evidence supporting their designation. A total of 18 sites were isolated as key amino acids by using multiple bioinformatics tools based on their concomitant functional divergence and positive selection. Almost all these key sites are located in 2 domains of this protein family where they exhibit no overlap with the structurally and functionally conserved sites. These results will provide an improved understanding of the complexity of the TPS gene family and of its function and evolution in higher plants. Moreover, this knowledge may facilitate the exploitation of these sites for protein engineering applications.